THE ANALYSIS OF TECHNOLOGY ADOPTION PROSPECT IN VIRTUAL TRY-ON EXPERIENCE TOWARDS ACCESSORIES BUSINESS - Levina Kerensa (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Augmented reality development has been growing significantly to help commercial industries in engaging with customers, providing new immersive experiences in shopping. With the rise of the global pandemic, more accessories businesses need to shift their activities into digital based. With the challenge in providing the best online shopping experience, augmented reality can be the solution tackling this challenge. This research wants to see the prospects of the adoption of augmented reality in the accessories industry by identifying the supporting factors and opposing factors of the technology adoption, along with recommendations to overcome the issues in augmented reality adoption. Through a qualitative method of in-depth interview research approach, this research collects the data by testing and validating the variables made based on the supporting theories from literature reviews with exploratory interviews with accessories business owners. By means of conducting data saturation and open coding, the findings based on the data analysis result can be confirmed that there are several concerns that affect augmented reality adoption that can be catered. This research has already made recommendations of improvements based on the insights and expects that augmented reality service providers can utilize this recommendation to provide better product development and innovation.